2021
DOI: 10.1039/d1md00244a
|View full text |Cite
|
Sign up to set email alerts
|

Phthalimide analogs for antimalarial drug discovery

Abstract: Malaria remains as one of the most life-threatening diseases and thus major public health concern all around the world. The disease becomes devastating if not treated with proper medication on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The interactions between N-11-azaartemisinins (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and heme in their entirety occur preferentially orienting Fe 2+ to heme. The distance d(Fe-O 1 ) is smaller than d(Fe-O 2 ) in all ligand-heme interactions and, in general, d(Fe-O1) has higher values for N-11-azaartemesinins cha, when compared to N-11-azaartemisinins cla.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interactions between N-11-azaartemisinins (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and heme in their entirety occur preferentially orienting Fe 2+ to heme. The distance d(Fe-O 1 ) is smaller than d(Fe-O 2 ) in all ligand-heme interactions and, in general, d(Fe-O1) has higher values for N-11-azaartemesinins cha, when compared to N-11-azaartemisinins cla.…”
Section: Discussionmentioning
confidence: 99%
“…The relative activities were obtained with the expression: relative IC 50 = IC 50 (artemisinin)/IC 50 (N-11-azaartemisinin) [51], where IC 50 corresponds to 50% of the inhibitory concentration of the compounds. The following hypothesis was considered in the research: N-11-azaartemisinins with relative IC50 ≥ 0.24 correspond to cha (1-8) and N-11-azaartemisinins with relative IC50 < 0.24 correspond to cla (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: About the Investigated N-11-azaartemisinismentioning
confidence: 99%
See 1 more Smart Citation
“…The novelty of this work comes from the synthesis of a novel isonitrile containing a phthalimido group (Pht) with plenty of desirable properties such as the presence of a protecting group, a pharmacophore moiety, and odorlessness as an extra bonus. Moreover, Pht-based compounds demonstrate therapeutic and pharmaceutical applications and thus function as leading points for the design of novel drug candidates, showing safe and effective anticancer and antimicrobial activities. Moreover, the Pht group participates in a vast number of potent anticancer drugs, such as thalidomide 1 , pomalidomide 2 , and lenalidomide 3 , and a strong anticonvulsant and antiepileptic drug, taltrimide 4 (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] It has been reported that phthalimide derivatives often exhibit diverse biological activities including antioxidant, 7 antimicrobial, 8 anti-cancer, 9,10 antiinflammatory, 11 antimalarial, etc. 12 For example, thalidomide, a widely used immunomodulatory drug, exhibits the highest in vivo anti-inflammatory activity. 13 With increasing interest in the activation of C-H bonds, several strategies for direct C-H amidation have been developed.…”
Section: Introductionmentioning
confidence: 99%